1952
DOI: 10.5962/bhl.part.21634
|View full text |Cite
|
Sign up to set email alerts
|

Mammals collected by Mr. Shaw Mayer in New Guinea, 1932-1949

Abstract: This paper gives a detailed account of a large collection of Mammals, mainly Marsupials and Rodents, from north-east New Guinea and eastern Papua (south-east New Guinea). Comparative descriptions are made of 13 new forms comprising i new genus (rodent), 7 new species (3 marsupials, 2 rodents, i bat, and i monotreme), and 5 subspecies (3 marsupials and 2 rodents).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 0 publications
1
30
0
Order By: Relevance
“…There are five valid species of Microperoryctes: M. murina Stein, 1932; M. longicauda (Peters & Doria, 1876); M. ornata (Thomas, 1904); M. papuensis (Laurie, 1952); M. aplini new species ( Fig. 1, Table 1).…”
Section: Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…There are five valid species of Microperoryctes: M. murina Stein, 1932; M. longicauda (Peters & Doria, 1876); M. ornata (Thomas, 1904); M. papuensis (Laurie, 1952); M. aplini new species ( Fig. 1, Table 1).…”
Section: Contentmentioning
confidence: 99%
“…This traditional scheme is modified here by describing M. aplini as a new species distinct from M. murina, and by recognizing both M. longicauda and M. ornata, previously considered conspecific, as two separate biological species. Microperoryctes longicauda has traditionally been divided into three or four subspecies that are thought to form a stepped cline in coloration from west to east (see Tate, 1948;Laurie, 1952;George & Maynes, 1990;Flannery, 1995;Westerman, Springer & Krajewski, 2001;Groves, 2005). These are M. l. longicauda of the Vogelkop Peninsula, which lacks a dorsal stripe and rump stripes; M. l. dorsalis of the western Central Cordillera (from the Weyland Range to the Strickland River), which generally possesses a moderately pronounced dorsal stripe but lacks rump stripes; and M. l. ornata and M. l. magna of east-central and southeastern New Guinea, respectively, which are boldly patterned with a dorsal stripe and lateral rump stripes.…”
Section: Contentmentioning
confidence: 99%
“…The second exception is the ''Ecological check-list of New Guinea Recent mammals'' by Ziegler (1982: 880) where in the account of ''Pogonomelomys ruemmleri,'' he indicated that the species included Rattus shawmayeri. Finally, by 1993 Musser andCarleton (1993: 585) formally recognized shawmayeri as a synonym of C. ruemmleri as a result of Musser's visits to BMNH where he studied the holotype and specimens reported by Laurie (1952); this allocation was repeated in 2005 Carleton, 2005: 1307 Whether the Telefomin region is the actual western limit of C. shawmayeri's range is unknown. It is not present in the material collected by the Archbold Expedition on the northern slopes of the Snow Mountains far to the west of the Telefomin area.…”
Section: Coccymys Ruemmlerimentioning
confidence: 99%
“…Taylor et al (1982) did not include it in their revision of Rattus from the New Guinea region, because, they noted, ''A study by J.A. Mahoney of the holotype and only known specimen has shown it to be an example of ruemmleri Tate and Archbold, 1941, a species now listed in Pogonomelomys, apparently failed to examine the holotype of shawmayeri or any of the BMNH specimens identified as that taxon by Laurie (1952) for his revision of Coccymys ruemmleri, as none are included in his list of material examined or anywhere in his report. Neither of Flannery's (1990Flannery's ( , 1995 editions of ''Mammals of New Guinea'' referred to shawmayeri in any context, even as a synonym of ruemmleri.…”
Section: Coccymys Ruemmlerimentioning
confidence: 99%
“…In addition to Leptomys paulus, eight mam-mal species are known only from the montane forests of the Papuan Peninsula, and three lowland species, the vespertilionid bat Pharotis imogene Thomas, 1914, the bandicoot Peroryctes broadbenti (Ramsay, 1879), and the murine Chiruromys forbesi Thomas, 1888, are endemic to the peninsula. Besides L. paulus, the montane endemics comprise the dasyure Murexia rothschildi Tate, 1938; the bandicoot Microperoryctes papuensis (Laurie, 1952;Aplin and Woolley, 1993); and the murines Chiruromys lamia (Thomas, 1897), Rattus vandeuseni Taylor andCalaby, 1982, Pseudohydromys germani (Helgen, 2005a), and as yet unnamed species of Pseudohydromys (see Helgen, 2007b) and Coccymys (Musser and Lunde, 1908;Musser and Carleton, 2005). Ongoing taxonomic studies continue to clarify the standing of these mountains as a significant zone of mammalian endemism (Flannery, 1995: 36-37;Helgen, 2007b).…”
Section: Zoogeographymentioning
confidence: 99%